Analisis Kebijakan Dinamika Kelembagaan Pendidikan Islam: Pesantren, Madrasah, dan Sekolah Islam terpadu di Indonesia: Studi komparatif - Mahyerni (Institut Agama Islam Hidayatullah Batam, 2023)
Islamic education is in the national education system, can be divided into three things. The first is Islamic education as an institution, the second is Islamic education as a subject, and the third is Islamic education as a value. The purpose of this research is to find out the Policy Analysis of Islamic Education Institutional Dynamics: Islamic Boarding Schools, Madrasas, and Integrated Islamic Schools in Indonesia: A Comparative Study. The method used in this research is the method used in this research is a qualitative method with a document review. In terms of this research is referred to as literature study research, by examining journals, books, research reports, magazines and other literature that is in accordance with the discussions studied in the study. Pondok pesantren is defined as a place to live as well as a place for students to gain knowledge, especially religious knowledge. The development of the pesantren curriculum can use strategies that do not undermine the characteristics of the pesantren as traditional Islamic religious education institutions. Madrasas as Islamic educational institutions are now placed as school education in the national education system. In one of the dictums of the joint decree (SKB) of three ministers (Minister of Religion, Minister of Education and Minister of Home Affairs) it was stated that steps were needed to improve the quality of education in madrasas so that graduates from madrasas could continue to public schools, from public schools elementary to college. In essence, an integrated Islamic school is a school that implements the concept of Islamic education based on the Qur'an and As Sunnah. The operational concept of SIT is an accumulation of processes of acculturation, inheritance and development of Islamic religious teachings, Islamic culture and civilization from generation to generation.